Peningkatan Pengetahuan Berbasis Bukti Ilmiah tentang Perilaku Budaya Bepidara dalam Penanganan Demam pada Masyarakat Banjar - Hardiyanti, Diana; Heryyanoor, Heryyanoor; Restu Pertiwi, Melinda; Maulidawati, Maulidawati; Norasiah, Norasiah (Jurnal SOLMA, 2024)
Background: The behavior of bepidara in treating fever for the Banjar community is local wisdom. However, many people still don't know about the scientific evidence related to bepidara. Objective: This community service aimed to increase scientific, evidence-based knowledge about bepidara cultural behaviour in treating fever in Banjar communities. Method: This activity implemented health education through socialization and interactive discussions about scientific evidence of cultural behaviour in treating fever. Data collection was carried out in stages, namely pre-test and post-test, using instruments in questionnaires for 33 respondents. Data analysis was conducted using categorical frequency distribution tables and paired t-test/Wilcoxon statistical tests. Results: There was an increase in respondents' knowledge about scientific evidence of cultural behavior in handling fever before and after being given health education, both in the excellent category from 0% to 79% or from an average score of 2 to 7.5. Meanwhile, in analysis using statistical tests, the value of p=0.001 (p<0.005) was obtained, which means that the health education provided impacted increasing knowledge. Conclusion: There was an increase in respondents' knowledge about scientific evidence of bepidara cultural behavior in treating fever in Banjar communities after being given health education.